Mizwala in the Islamic Tradition: A Historical Overview, Its Contributions, and Its Relevance in the Contemporary Era - Sukarni Sukarni; Ahmad Izzuddin; Fitriyatul Laili (Islamic Astronomy Department, Sharia and Law Faculty, 2026)
This study explores the history, contribution, and contemporary relevance of the mizwala (sundial) in the development of Islamic astronomy (‘ilm al-falak). The mizwala is a classical astronomical instrument used by Muslim scholars since the 9th century CE to determine the direction of the qibla and prayer times based on the position of the sun. The aim of this research is to retrace the scientific foundations of Islamic astronomy and to highlight the continuity between classical Islamic science and modern knowledge. The research adopts a qualitative-descriptive method with historical and analytical approaches through the examination of primary and secondary literature. The findings reveal that the mizwala functioned not only as a scientific measuring device but also as a symbol of the integration between scientific inquiry and religious devotion in Islamic tradition. In contemporary contexts, the mizwala remains relevant as a verification tool for qibla direction and as an educational medium for practical astronomy. Moreover, it represents a sustainable technology that operates solely using solar energy, independent of digital systems. Therefore, preserving and revitalizing the mizwala is crucial to maintaining the continuity of Islamic scientific heritage while fostering innovation in modern astronomical studies.